2018
DOI: 10.1136/heartjnl-2018-313634
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers to diagnose ventricular dysfunction in childhood cancer survivors: a systematic review

Abstract: In individual studies, the diagnostic value of NT-proBNP for detection of LV dysfunction in CCS is limited. Troponins have no role in detecting late-onset LV dysfunction with cut-off values as low as 0.01 ng/mL. Further study on optimal NT-proBNP cut-off values for rule out or rule in of LV dysfunction is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 39 publications
7
25
0
Order By: Relevance
“…NT-proBNP levels did not differ significantly by prior CRT, which is in agreement with an improved ability of novel echocardiographic methods to better detect late subclinical LV dysfunction in asymptomatic childhood cancer survivors than natriuretic peptides assays [32,33,34]. Moreover, the superiority of novel echocardiographic techniques, i.e., global longitudinal strain analysis and tissue Doppler imaging, over conventional parameters to detect systolic [7,8] and diastolic [6,10] LV dysfunction has previously been demonstrated in long-term survivors of childhood cancer, mainly after ALL.…”
Section: Discussionsupporting
confidence: 71%
“…NT-proBNP levels did not differ significantly by prior CRT, which is in agreement with an improved ability of novel echocardiographic methods to better detect late subclinical LV dysfunction in asymptomatic childhood cancer survivors than natriuretic peptides assays [32,33,34]. Moreover, the superiority of novel echocardiographic techniques, i.e., global longitudinal strain analysis and tissue Doppler imaging, over conventional parameters to detect systolic [7,8] and diastolic [6,10] LV dysfunction has previously been demonstrated in long-term survivors of childhood cancer, mainly after ALL.…”
Section: Discussionsupporting
confidence: 71%
“…Early detection provides opportunities for interventions to preserve systolic function and potentially limit heart failure–associated morbidity and mortality; this is similar to findings observed in the general population 6,7 . However, prior studies have been unsuccessful at identifying early markers of developing cardiac dysfunction in the childhood cancer survivor population 3,8 …”
Section: Introductionmentioning
confidence: 56%
“…Prior cross‐sectional studies focusing on the diagnostic yield of surveillance for cardiomyopathy in asymptomatic childhood cancer survivors have suggested that natriuretic peptides are inadequate as the only method of surveillance because of their low sensitivity and positive predictive value for the detection of current cardiomyopathy 3,8,11,12 . However, associations with future major cardiac events and death have not been systematically assessed in a large cohort of long‐term adult survivors of childhood cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The strain analysis may benefit the early identification of cardiotoxicity in childhood cancer patients, but only few studies covered myocardial strain for an early diagnosis of LV dysfunction . At present, systematic evidence on the role of biomarkers for cardiotoxicity in childhood cancer patients is limited with one available systematic review that did not assess acute/subacute cardiotoxicity seen within <1 year after the beginning of cancer therapy …”
Section: Discussionmentioning
confidence: 99%